MENINGKATKAN INTERAKSI SOSIAL ANAK AUTISME TERHADAP TEMAN SEBAYANYA - Elisa Simatupang; Rotua Simanjuntak; Imma Niani Gulo (CV. ADIBA AISHA AMIRA, 2024)
Children with autism often face difficulties in social interactions with their peers, which can affect their social and emotional development. In this article, we discuss effective strategies for improving children with autism's social interactions with their peers. With a holistic approach and the right support from the surrounding environment, including family, teachers and therapists, children with autism can develop their social skills. This research uses a qualitative descriptive method with interview data collection techniques and analyzing related journals and articles, the number of respondents is 1 person, namely the child's parents, the research location is at the Happy Oppung boarding house on Green Lane number 83 Medan, the aim is how to increase the social interaction of children with autism Towards Peers.